Caper bush (Capparis spinosa L.) bioactive compounds and antioxidant capacity as affected by adaptation to harsh soils - Elham Yousefi; Mehdi Abedi; Tahereh A. Aghajanzadeh; Diego A. Moreno (Scientific Reports)
Abstract Caper bush (Capparis spinosa) is a naturally grown species in different soils. To gain insight into the impact of various soil conditions on nutritional and phytochemical properties, aerial parts of caper bush (C. spinosa) were collected from gypsum and non-gypsum soils in southern Iran. Colorimetric analyses of antioxidant compounds (total phenolics and flavonoids) and antioxidant capacity tests (DPPH, FRAP, ABTS) were carried out, and intact aliphatic and indolic glucosinolates (predominant aliphatic glucocapparin) were analyzed by HPLC-DAD method. Based on the findings, plant parts and sites significantly impacted most parameters. The highest TPC values were observed in the petals in gypsum soil and the lowest in the non-gypsum soil seeds by 2317.78 and 635.06 mg/kg FW, respectively. Likewise, the highest TFC was recorded in the non-gypsum soil leaves and the lowest in the non-gypsum soil seeds by 401.06 and 55.61 Qu mg/kg FW, respectively. The highest and lowest FRAP values were observed in the leaves in gypsum (0.94) and the pistils in gypsum soil (0.80), respectively. Regarding ABTS values, the flags in the non-gypsum and gypsum sites showed the highest and lowest values of 89.51 and 78.40%, respectively. High DPPH values were recorded for most parts. The highest amount of glucocapparin was found in the pistils in gypsum, and the lowest was in the petals in gypsum soil by 35.81 and 21.65 µmol/g DW, respectively. The gypsum sites showed higher values for most of the studied parameters. The PCA results showed that pistils were associated with glucocapparin, petals with DPPH, and the leaves and sepals with TPC, FRAP, ABTS, and TFC. The majority of studied factors correlated well with TPC. Our results supported the potential of caper bush (C. spinosa) as a underexploited food rich in bioactivephytochemicals adapted to harsh soil conditions, with the potential for implementation in agroecosystems with adverse environmental conditions with the potential of better adaptation for securing the access to plant-derived foods.